The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fcell.2021.671022
|View full text |Cite
|
Sign up to set email alerts
|

WNT Ligand Dependencies in Pancreatic Cancer

Abstract: WNT signaling promotes the initiation and progression of pancreatic ductal adenocarcinoma (PDAC) through wide-ranging effects on cellular proliferation, survival, differentiation, stemness, and tumor microenvironment. Of therapeutic interest is a genetically defined subset of PDAC known to have increased WNT/β-catenin transcriptional activity, growth dependency on WNT ligand signaling, and response to pharmacologic inhibitors of the WNT pathway. Here we review mechanisms underlying WNT ligand addiction in panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 74 publications
0
35
0
Order By: Relevance
“…1 C). The growth factor receptors and frizzled receptors are well characterized as contributors to PDAC tumor development [ 18 , 19 ]. The formyl peptide receptors are expressed in phagocytes and a recent study showed that the ANXA1 – FPRs pathway promotes PDAC metastasis [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 C). The growth factor receptors and frizzled receptors are well characterized as contributors to PDAC tumor development [ 18 , 19 ]. The formyl peptide receptors are expressed in phagocytes and a recent study showed that the ANXA1 – FPRs pathway promotes PDAC metastasis [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…DpC also inhibited PSC activation in vitro and reduced desmoplasia in vivo ( 48 ). The current study mechanistically dissected for the first time the effects of the metastasis suppressor, NDRG1, and the NDRG1-inducing thiosemicarbazones on more recently identified key mediators of cross talk between PC cells and PSCs, namely TGF-β, TnC, Wnt/β-catenin, and YAP/TAZ ( 12 , 97 , 114 , 115 , 116 ). In fact, TnC is highly elevated in invasive PC and produced by activated PSCs ( 35 , 117 ), leading to activation of oncogenic Wnt/β-catenin and YAP/TAZ pathways ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…WNT ligand signaling plays key roles in PDAC initiation, progression, dissemination, and therapeutic resistance. Therapeutic interest is a genetically defined subset of PDAC known to have increased WNT/β‐catenin transcriptional activity, growth dependency on WNT ligand signaling, and response to pharmacologic inhibitors of the WNT pathway (Aguilera & Dawson, 2021).…”
Section: Discussionmentioning
confidence: 99%